PENERAPAN MEDIA GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR PJOK SISWA KELAS IV SD NEGERI 004 TEMBILAHAN KOTA KECAMATAN TEMBILAHAN - Muharis (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
This study is peneilitian class action was motivated by the low learning PJKO fourth grade students SD Negeri 004 Tembilahan Kota. This is evident from the acquisition value of the average students who are still under the KKM is equal to 56,00 being KKM specified value is 61, other than that of the 20 students only 7 (35.00%) students who completed their study results. Based on this the researchers applied media with the aim of improving student learning outcomes PJOK. This classroom action research conducted in SD Negeri 004 Tembilahan Kota in the fourth grade with the number of students 20 students, the study was conducted 2 cycles and be done with four stages: planning, implementation, observation, and reflection. The results showed that after the implementation of learning media, learning outcomes PJOK increase, evidenced by the acquisition: "At the initial data is the number of students who completed 7 students (35.00%) with an average nilaia 56.00, in the first cycle increased by the number of students who completed totaling 13 students (65.00%) with the average value of students increased to 72.50. And the second cycle learning outcomes increased with the number of students who completed the acquisition of up to 19 students (95.00%) with the acquisition value by an average of 83.25. Based on this acquisition can be concluded that the application of instructional media can improve learning outcomes PJOK fourth grade students SD Negeri 004 Tembilahan Kota.